The proportion of chronic kidney disease and its associated factors among adult diabetic patients at Tibebe Ghion Specialized Hospital, Bahir Dar, Ethiopia - Daniel Tesfe; Mesert Adugna; Zelalem Mehari Nigussie; Alem Endeshaw Woldeyohanins; Zemene Demelash Kifle (Metabolism Open, 2022)
Background: Chronic kidney disease is defined as a progressive loss of kidney function occurring over several months to years. Programs to detect chronic kidney disease, linked to comprehensive primary and secondary Prevention strategies are rare in our country. This study aimed to assess the proportion of chronic kidney disease and its associated factors among adult diabetic patients. Methods: An institutional-based cross-sectional study design was used. Adult Diabetic Patients (≥18 years of age) coming to the medical outpatient clinic were considered as study participants and they were selected using a systematic random sampling technique. Data were checked for completeness, then entered into Epi Data 3.1, and exported to SPSS Version 24 for analysis. Descriptive statistics such as frequency, crosstab, and median were utilized. chronic kidney disease epidemiology collaboration equations for calculating estimated glomerular filtration rate Simple binary logistic regression was conducted to identify candidate variables for multiple binary logistic regression at a p-value of <0.2. Those variables whose P-value <0.05 in multiple binary logistic regression were considered as significantly associated variables with chronic kidney diseases. Result: A total of 329 individuals were participating in the study. Of which 199 (60.5%) were males. The median age of participants was 39 (IQR; 28: 56) years. Of the total participants, 125(38%) had no formal education. The proportion of chronic kidney disease was 16.7% (95% CI: 12.8%–21%), The study also found that older age (AOR = 3.02; 95%CI: 1.37, 6.69), pre-existing hypertension (AOR = 4.85; 95%CI: 2.07, 11.3), current systolic blood pressure ≥140mmHg (AOR = 6.33, 95%CI: 3.34, 11.99), and presence of Albuminuria (AOR = 2.98, 95%CI: 1.26, 7.09) were associated with chronic kidney disease. Conclusions: The proportion of CKD among diabetic patients in Tibebe Ghion Specialized Hospital was relatively high as compared to other studies. Health care professionals should consider strict follow-up for older age patients, patients with co-morbidities like hypertension, and for those patients with Albuminuria.